1957
DOI: 10.1111/j.1476-5381.1957.tb01367.x
|View full text |Cite
|
Sign up to set email alerts
|

The Transmitter Released by Stimulation of the Bronchial Sympathetic Nerves of Cats

Abstract: A study has been made of the transmitter released in a cat heart-lung preparation when the sympathetic chains were stimulated. The nervi accelerantes were always sectioned before stimulation. The transmitter appeared first in the pulmonary venous blood. In its actions on the heart-lung preparation, it resembled isoprenaline and not adrenaline. Chromatographic studies using three different solvents showed that 80 to 100% of this transmitter consisted of a catechol amine which had R, values which were identical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1959
1959
1979
1979

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…The evidence that the bronchodilator fibres are adrenergic is mainly pharmacological. Lockett (1957) observed that the sympathetic bronchodilator fibres can be blocked by compound TM-1O (Choline 2: 6-xylyl ether bromide), which is thought to act by preventing the release of the transmitter substance. Daly & Mount (1951) noted that response to stimulation of the bronchodilator fibres can be potentiated by cocaine, an effect thought to be mediated by an action on the adrenergic fibres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence that the bronchodilator fibres are adrenergic is mainly pharmacological. Lockett (1957) observed that the sympathetic bronchodilator fibres can be blocked by compound TM-1O (Choline 2: 6-xylyl ether bromide), which is thought to act by preventing the release of the transmitter substance. Daly & Mount (1951) noted that response to stimulation of the bronchodilator fibres can be potentiated by cocaine, an effect thought to be mediated by an action on the adrenergic fibres.…”
Section: Discussionmentioning
confidence: 99%
“…Daly & Mount (1951) noted that response to stimulation of the bronchodilator fibres can be potentiated by cocaine, an effect thought to be mediated by an action on the adrenergic fibres. Furthermore, Lockett (1957) has reported the release of an isoprenaline-like substance in the perfusate of the cat heart-lung preparation, following electrical stimulation of the thoracic sympathetic chain. Muscholl & Vogt (1958), however, used more stringent methods of identification and were unable to confirm the release of isoprenaline.…”
Section: Discussionmentioning
confidence: 99%
“…Since trace amounts of this amine have been reported in the adrenal glands of the cat, monkey and man (Lockett, 1954) and in the pulmonary venous blood of cats after stimulation of the cervical sympathetic chain (Lockett, 1957), a more detailed study has been made of its circulatory, respiratory and metabolic effects in man; a preliminary summary of the findings has already been reported (Cobbold, Galbraith, Ginsburg & Paton, 1958). …”
mentioning
confidence: 99%
“…Further, urotensin does not act by causing a prolonged release of acetylcholine, histamine or an isoprenaline-like metabolite of adrenaline. Such a metabolite of adrenaline has been shown to be present in extracts of mammalian adrenal medulla (Lockett, 1954), in extracts of protein-free plasma of rabbits (Roberts & Lockett, 1961), or released in a cat heart-lung preparation after stimulation of sympathetic chains (Lockett, 1957).…”
Section: Discussionmentioning
confidence: 99%